VOZ1 and VOZ2 transcription factors regulate arsenic tolerance and distribution in rice and Arabidopsis - Wen, Ying; Chairattanawat, Chayanee; Vo, Kieu Thi Xuan; Liu, Jiayou; Zhang, Jie; Pan, Ting; Kim, Do-Young; Martinoia, Enrico; Zhong, Chun-Yan; Wang, Mao-Hui; Jeon, Jong-Seong; Song, Won-Yong (Frontiers in Plant Science, 2023)
Rice is the major source of arsenic (As) intake in humans, as this staple crop readily accumulates As in the grain. Identifying the genes and molecular mechanisms underlying As accumulation and tolerance is a crucial step towards developing rice with reduced As levels. We identified 25 rice genes that improve As tolerance in yeast cells by expressing a cDNA library generated from Astreated rice roots. Among them, a zinc finger-type transcription factor OsVOZ1 conferred the most pronounced As tolerance. OsVOZ1 inhibits As accumulation in yeast via activation of As efflux transporter Acr3p by post transcriptional modification in yeast. The Arabidopsis voz1 voz2 double knockout mutant exhibited As hypersensitivity, altered As concentrations in various tissues, and reduced As transport activity via the phloem. Arabidopsis and rice VOZs were highly expressed in phloem cells in various tissues, which are critical for As distribution in plant tissues. The double knockdown and single knockout plants of OsVOZ1 and OsVOZ2 reduced As accumulation in their seeds. These findings suggest that rice and Arabidopsis VOZs regulate the translocation of As into tissues by regulating the phloem loading of this element.